Electrochemical nitrate reduction in acid enables high-efficiency ammonia synthesis and high-voltage pollutes-based fuel cells - Zhang, Rong; Li, Chuan; Cui, Huilin; Wang, Yanbo; Zhang, Shaoce; Li, Pei; Hou, Yue; Guo, Ying; Liang, Guojin; Huang, Zhaodong; Peng, Chao; Zhi, Chunyi (Nature communications, 2023)
Most current research is devoted to electrochemical nitrate reduction reaction for ammonia synthesis under alkaline/neutral media while the investigation of nitrate reduction under acidic conditions is rarely reported. In this work, we demonstrate the potential of TiO 2 nanosheet with intrinsically poor hydrogen-evolution activity for selective and rapid nitrate reduction to ammonia under acidic conditions. Hybridized with iron phthalocyanine, the resulting catalyst displays remarkably improved efficiency toward ammonia formation owing to the enhanced nitrate adsorption, suppressed hydrogen evolution and lowered energy barrier for the rate-determining step. Then, an alkaline-acid hybrid Zn-nitrate battery was developed with high open-circuit voltage of 1.99 V and power density of 91.4 mW cm –2 . Further, the environmental sulfur recovery can be powered by above hybrid battery and the hydrazine-nitrate fuel cell can be developed for simultaneously hydrazine/nitrate conversion and electricity generation. This work demonstrates the attractive potential of acidic nitrate reduction for ammonia electrosynthesis and broadens the field of energy conversion. Research on electrochemical nitrate reduction to ammonia in acidic conditions has been less extensive than that conducted in alkaline conditions. Here, the authors report a hybrid of iron phthalocyanine and TiO 2 catalyst with improved efficiency toward acidic nitrate reduction and its application in Zn-nitrate batteries and high-voltage pollutes-based fuel cell.